Problematic Aspects of Professional Competence of Educational Management ("Journal "U". Economy. Management. Finance.", 2021)
The article is devoted to the problematic aspects of the professional competence of educational management. The relevance of the article is due to the fact that at the moment special attention is paid to management as the main factor in the productive activities of enterprises. Accordingly, the concept of training managers in modern conditions requires certain changes. The views on the well-known provisions of the essential characteristics of the categories of management are analyzed; highlighted the latest principles of management of educational activities; describes the competencies of managers for educational activities.
Keywords: management in education; management of education; competence of a manager in education; management model; activities of a manager in education